(untitled) (Studium, 2018)
Cuentas y materiales utilizados en la construcción de la iglesia de San Juan de los Panetes de Zaragoza, según seis albaranes de pago a los maestros que intervinieron en las obras. Palabras clave. Orden de San Juan de Jerusalén. Iglesia de San Juan de los Panetes (Zaragoza). Blas Ximénez. Pedro Izaguirre. Francisco de Urbieta. Domingo Sastre. Tomás de Mesa. Lorenzo Arbex. Abstract. Accountancy and materials used in the construction of the church of Saint John de los Panetes, in Zaragoza, according to six slips with the payment to the master builders who took part in the works. Key Words Order of Knights of the Hospital of Saint John of Jerusalem. Church of Saint John de los Panetes (Zaragoza). Blas Ximénez. Pedro Izaguirre. Francisco de Urbieta. Domingo Sastre. Tomás de Mesa. Lorenzo Arbex